Educational Outcomes of Childhood Survivors of Critical Illness—A Population-Based Linkage Study*. Issue 6 (16th February 2022) - Tomaszewski, Wojtek; Ablaza, Christine; Straney, Lahn; Taylor, Catherine; Millar, Johnny; Schlapbach, Luregn J.; ,
Abstract : OBJECTIVES: Major postintensive care sequelae affect up to one in three adult survivors of critical illness. Large cohorts on educational outcomes after pediatric intensive care are lacking. We assessed primary school educational outcomes in a statewide cohort of children who survived PICU during childhood. DESIGN: Multicenter population-based study on children less than 5 years admitted to PICU. Using the National Assessment Program—Literacy and Numeracy database, the primary outcome was educational achievement below the National Minimum Standard (NMS) in year 3 of primary school. Cases were compared with controls matched for calendar year, grade, birth cohort, sex, socioeconomic status, Aboriginal and Torres Strait Islander status, and school. Multivariable logistic regression models to predict educational outcomes were derived. SETTING: Tertiary PICUs and mixed ICUs in Queensland, Australia. PATIENTS: Children less than 5 years admitted to PICU between 1998 and 2016. INTERVENTIONS: Not applicable. MEASUREMENTS AND MAIN RESULTS: Year 3 primary school data were available for 5, 017 PICU survivors (median age, 8.0 mo at first PICU admission; interquartile range, 1.9–25.2). PICU survivors scored significantly lower than controls across each domain ( p < 0.001); 14.03% of PICU survivors did not meet the NMS compared with 8.96% of matched controls ( p < 0.001). In multivariate analyses, socioeconomic status (odds ratio, 2.14; 95% CI, 1.67–2.74), weight (0.94; 0.90–0.97), logit of Pediatric Index of Mortality-2 score (1.11; 1.03–1.19), presence of a syndrome (11.58; 8.87–15.11), prematurity (1.54; 1.09–2.19), chronic neurologic conditions (4.38; 3.27–5.87), chronic respiratory conditions (1.65; 1.24–2.19), and continuous renal replacement therapy (4.20; 1.40–12.55) were independently associated with a higher risk of not meeting the NMS. CONCLUSIONS: In this population-based study of childhood PICU survivors, 14.03% did not meet NMSs in the standardized primary school assessment. Socioeconomic status, underlying diseases, and severity on presentation allow risk-stratification to identify children most likely to benefit from individual follow-up and support.